Porous high-wettability lithium battery diaphragm as well as preparation method and application thereof
By loading polymer materials with porous structures on the lithium battery separator, the problem of difficult electrolytes in traditional separators is solved, and the ion transfer rate and overall performance of lithium-ion batteries are improved.
Patent Information
- Application Number
- CN202411416711.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-13
AI Technical Summary
The pore size distribution of traditional polyolefin lithium batteries is uneven, which makes it difficult for electrolytes to be effectively infiltrated, affecting the uniform transmission of lithium ions and battery reaction rate, and threatening battery safety and performance.
Imidazole or thiazole organic small molecules are hydrothermal reaction with oxidants and iron salts to form polymer materials, and are loaded onto the polyolefin separator to form a porous structure, which improves the wettability and ion transfer rate of the separator.
It significantly improves the ion transfer rate during charging and discharging of lithium-ion batteries, enhances the breathability, wetting and thermal conductivity of the diaphragm, and improves the overall performance of the battery.
Smart Images

Figure CN119133771A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery separators, and in particular relates to a porous high-wettability lithium ion battery separator and a preparation method and application thereof. Background Art
[0002] With the decreasing supply of traditional fossil energy and the increasing awareness of environmental protection, lithium-ion batteries, as a convenient, clean and efficient energy storage device, have gained more and more attention and development. After continuous exploration by scientific research institutions and social organizations in various countries, lithium-ion batteries have been widely used in electric vehicles, digital home appliances, smart phones, wind and solar energy storage and other fields.
[0003] The separator is one of the indispensable components in the structure of lithium-ion batteries. It can effectively isolate the contact between the positive and negative electrodes, prevent battery short circuit, and realize the transmission of electrolyte ions. Its structure and performance affect the internal resistance of the battery, the bonding with the pole piece, the safety and performance of the battery, etc.
[0004] The uneven pore size distribution of traditional polyolefin lithium battery separators affects the uniform transmission and deintercalation of lithium ions, and may even produce serious lithium dendrites, threatening the safety of the battery. In addition, it is difficult for electrolytes to effectively infiltrate traditional polyolefin separators, which slows down the transmission speed of ions inside the battery and the reaction rate, resulting in the battery being unable to perform at its designed capacity. Summary of the invention
[0005] The technical problem to be solved by the present invention is how to solve the problem that the electrolyte is difficult to infiltrate the polyolefin separator.
[0006] The present invention solves the above technical problems through the following technical means:
[0007] The first aspect of the present invention provides a porous high-wettability lithium battery separator, comprising a polyolefin separator and a polymer material loaded on the polyolefin separator; the polymer material is obtained by adding imidazole or thiazole organic small molecules to an oxidant solution for hydrothermal reaction, and then adding iron salt for polymerization reaction, and the oxidant is sodium hypochlorite, sodium chlorite and hydrogen peroxide.
[0008] Beneficial effects: The polymer material of the present invention itself has a hydrophilic group and a porous structure. The polymer material is loaded on a polyolefin diaphragm, which effectively improves the wettability of the diaphragm and increases the ion transfer rate during the charge and discharge process of the lithium-ion battery.
[0009] Preferably, the imidazole or thiazole organic small molecule includes one or more of imidazole, thiazole, N-methylimidazole, 2-methylimidazole, 2-phenylimidazole, 2-aminothiazole, 4-methylimidazole, 4-aminothiazole, 5-methylimidazole, and 2-amino-5-methylthiazole.
[0010] More preferably, any one or more of N-methylimidazole, 2-methylimidazole, 2-phenylimidazole, and 2-aminothiazole.
[0011] Preferably, the iron salt is ferric chloride or ferric sulfate.
[0012] The second aspect of the present invention provides a method for preparing a porous high-wettability lithium battery separator, comprising the following steps:
[0013] (1) Preparation of polymer materials: adding imidazole or thiazole organic small molecules to sodium hypochlorite solution for hydrothermal reaction, and then adding iron salt for polymerization reaction;
[0014] (2) Preparing a porous and highly wettable lithium battery separator: The polymer material prepared in step (1) is stirred and evenly mixed with a dispersant and a binder in a solvent to obtain a coating slurry, and the coating slurry is then coated on a polyolefin separator and dried to obtain a porous and highly wettable lithium ion battery separator.
[0015] Beneficial effects: The porous high-wettability lithium-ion battery separator prepared by the present invention has high air permeability, good wettability, small contact angle, strong thermal conductivity, and has the advantages of being porous, highly wettable, electrolyte-philic, and high-performance.
[0016] Preferably, the hydrothermal reaction time is 12-48 hours, and the hydrothermal reaction temperature is 90-150°C; the polymerization reaction time is 0.5-3 hours, and the polymerization reaction temperature is 700-1000°C.
[0017] Preferably, the mass ratio of the organic small molecule: sodium hypochlorite: iron salt is (10-20): (8-18): (9-22).
[0018] Preferably, the dispersant includes one or more of polyacrylate, polyacrylate, polyethylene glycol, and polyvinyl pyrrolidone; the adhesive includes one or more of polyvinylidene fluoride, styrene-butadiene rubber, acrylonitrile multipolymer, polyvinyl alcohol, polyacrylic acid, polypropylene alcohol, acrylic adhesive, and vinyl acetate adhesive; the solvent includes one or more of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, dichloromethane, chloroform, N-methylpyrrolidone, dimethyl sulfoxide, cyclohexane, water, and ethanol.
[0019] Preferably, the coating slurry contains 50-90 wt % of polymer material, 5-20 wt % of dispersant and 5-25 wt % of binder.
[0020] Preferably, the polyolefin membrane is one or more of a single-layer polypropylene porous membrane, a single-layer polyethylene porous membrane, a multi-layer polyethylene microporous membrane, and a polypropylene-polyethylene multi-layer composite membrane; the coating method includes one of blade coating, roller coating, spray coating, spin coating, filtration, casting, and hot pressing.
[0021] Preferably, the thickness of the polyolefin separator is 5-25 μm; and the coating thickness is 0.5-20 μm.
[0022] The third aspect of the present invention provides a method for preparing the porous high-wettability lithium battery separator and application of the prepared porous high-wettability lithium battery separator in lithium batteries.
[0023] Beneficial effects: The polymer material of the present invention itself has a hydrophilic group and a porous structure. The polymer material is loaded on a polyolefin diaphragm, which effectively improves the wettability of the diaphragm and increases the ion transfer rate during the charge and discharge process of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a microscopic morphology of a polymer material in a porous and highly wettable lithium battery separator in an embodiment. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0027] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0028] Example 1
[0029] This embodiment provides a porous high-wettability lithium battery separator and a preparation method, which are as follows:
[0030] (1) Preparation of polymer materials:
[0031] Dissolve 150g of 2-aminothiazole in 5000ml of water, add 1500ml of 8% sodium hypochlorite solution, mix well and transfer into a stainless steel autoclave lined with polytetrafluoroethylene, and perform hydrothermal reaction at 110°C for 24h; add 1000ml of 1mol / L ferric chloride solution to the product after hydrothermal reaction, dry it by rotary evaporation, and polymerize the dried product at 900°C under an inert atmosphere for 1h. After completion, use 1M hydrochloric acid solution at 80°C for 7.5h to obtain a polymer material. The microscopic morphology of the polymer material is shown in the figure below. Figure 1 shown.
[0032] (2) Preparation of coating slurry:
[0033] Add the polymer material prepared in step (1), polyethylene glycol and polyvinylidene fluoride into water, stir at high speed to mix evenly, and prepare a coating slurry; in the coating slurry, the polymer material content is 75wt%, the polyethylene glycol content is 12wt%, and the polyvinylidene fluoride content is 13wt%.
[0034] (3) Preparation of porous and highly wettable lithium battery separator:
[0035] The coating slurry obtained in step (2) is sprayed on a 16 μm thick single-layer polyethylene porous membrane, and the coating layer thickness is 4 μm. After oven drying, a porous high-wettability lithium battery separator is obtained.
[0036] Example 2
[0037] This embodiment provides a porous high-wettability lithium battery separator and a preparation method. The difference between this embodiment and Example 1 is that 2-aminothiazole is changed to 2-methylimidazole.
[0038] Example 3
[0039] This embodiment provides a porous high-wettability lithium battery separator and a preparation method. The difference between this embodiment and Example 1 is that 2-aminothiazole is changed to 2-phenylimidazole.
[0040] Example 4
[0041] This embodiment provides a porous high-wettability lithium battery separator and a preparation method. The difference between this embodiment and Example 1 is that 2-aminothiazole is changed to N-methylimidazole.
[0042] Example 5
[0043] This embodiment provides a porous high-wettability lithium battery separator and a preparation method, which are as follows:
[0044] (1) Preparation of polymer materials:
[0045] 150 g of 2-aminothiazole was dissolved in 5000 ml of water, and 1000 ml of 8% sodium hypochlorite solution was added. After mixing evenly, the mixture was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally reacted at 110° C. for 24 h. 1000 ml of 1 mol / L ferric chloride solution was added to the product after the hydrothermal reaction, and the product was dried by rotary evaporation. The dried product was annealed at 900° C. for 1 h under an inert atmosphere. After the annealing, a 1 M hydrochloric acid solution was used for pickling at 80° C. for 7.5 h to obtain a polymer material.
[0046] (2) Preparation of coating slurry:
[0047] Add the polymer material prepared in step (1), polyethylene glycol and polyvinylidene fluoride into water, stir at high speed to mix evenly, and prepare a coating slurry; in the coating slurry, the polymer material content is 75wt%, the polyethylene glycol content is 12wt%, and the polyvinylidene fluoride content is 13wt%.
[0048] (3) Preparation of porous and highly wettable lithium battery separator:
[0049] The coating slurry obtained in step (2) is roller-coated on a 10 μm thick single-layer polypropylene porous membrane, and the coating layer thickness is 2 μm. After being dried in an oven, a porous high-wettability lithium battery separator is prepared.
[0050] Example 6
[0051] This embodiment provides a porous high-wettability lithium battery separator and a preparation method, which are as follows:
[0052] (1) Preparation of polymer materials:
[0053] 150 g of 2-aminothiazole was dissolved in 5000 ml of water, and 1500 ml of 8% sodium hypochlorite solution was added. After mixing evenly, the mixture was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally reacted at 110° C. for 24 h. 800 ml of 1 mol / L ferric chloride solution was added to the product after the hydrothermal reaction, and the product was dried by rotary evaporation. The dried product was annealed at 900° C. for 1 h under an inert atmosphere. After the annealing, a 1 M hydrochloric acid solution was used for pickling at 80° C. for 7.5 h to obtain a polymer material.
[0054] (2) Preparation of coating slurry:
[0055] Add the polymer material prepared in step (1), polyethylene glycol and polyvinylidene fluoride into water, stir at high speed to mix evenly, and prepare a coating slurry; in the coating slurry, the polymer material content is 75wt%, the polyethylene glycol content is 12wt%, and the polyvinylidene fluoride content is 13wt%.
[0056] (3) Preparation of porous and highly wettable lithium battery separator:
[0057] The coating slurry obtained in step (2) is scraped onto a 20 μm thick single-layer polyethylene microporous membrane, and the coating layer thickness is 4 μm. After being dried in an oven, a porous and highly wettable lithium battery separator is prepared.
[0058] Example 7
[0059] This embodiment provides a porous high-wettability lithium battery separator and a preparation method, which are as follows:
[0060] (1) Preparation of polymer materials:
[0061] 100 g of 2-aminothiazole was dissolved in 5000 ml of water, and 1500 ml of 8% sodium hypochlorite solution was added. After mixing evenly, the mixture was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally reacted at 110° C. for 24 h. 1000 ml of 1 mol / L ferric chloride solution was added to the product after the hydrothermal reaction, and the product was dried by rotary evaporation. The dried product was annealed at 900° C. for 1 h under an inert atmosphere. After the annealing, a 1 M hydrochloric acid solution was used for pickling at 80° C. for 7.5 h to obtain a polymer material.
[0062] (2) Preparation of coating slurry:
[0063] Add the polymer material prepared in step (1), polyethylene glycol and polyvinylidene fluoride into water, stir at high speed to mix evenly, and prepare a coating slurry; in the coating slurry, the polymer material content is 75wt%, the polyethylene glycol content is 12wt%, and the polyvinylidene fluoride content is 13wt%.
[0064] (3) Preparation of porous and highly wettable lithium battery separator:
[0065] The coating slurry obtained in step (2) is spin-coated on a 25 μm thick polypropylene-polyethylene multilayer composite film, and the coating layer thickness is 4 μm. After being dried in an oven, a porous and highly wettable lithium battery separator is prepared.
[0066] Example 8
[0067] This embodiment provides a porous high-wettability lithium battery separator and a preparation method, which are as follows:
[0068] (1) Preparation of polymer materials:
[0069] 150 g of 2-aminothiazole was dissolved in 5000 ml of water, and 2000 ml of 8% sodium hypochlorite solution was added. After mixing evenly, the mixture was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally reacted at 110° C. for 24 h. 1000 ml of 1 mol / L ferric chloride solution was added to the product after the hydrothermal reaction, and the product was dried by rotary evaporation. The dried product was annealed at 900° C. for 1 h under an inert atmosphere. After the annealing, a 1 M hydrochloric acid solution was used for pickling at 80° C. for 7.5 h to obtain a polymer material.
[0070] (2) Preparation of coating slurry:
[0071] Add the polymer material prepared in step (1), polyethylene glycol and polyvinylidene fluoride into water, stir at high speed to mix evenly, and prepare a coating slurry; in the coating slurry, the polymer material content is 75wt%, the polyethylene glycol content is 12wt%, and the polyvinylidene fluoride content is 13wt%.
[0072] (3) Preparation of porous and highly wettable lithium battery separator:
[0073] The coating slurry prepared in step (2) is sprayed on a 16 μm thick single-layer polyethylene porous membrane, and the coating layer thickness is 4 μm. After being dried in an oven, a porous high-wettability lithium battery separator is prepared.
[0074] Example 9
[0075] This embodiment provides a porous high-wettability lithium battery separator and a preparation method, which are as follows:
[0076] (1) Preparation of polymer materials:
[0077] 150 g of 2-aminothiazole was dissolved in 5000 ml of water, and 1500 ml of 8% sodium hypochlorite solution was added. After mixing evenly, the mixture was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally reacted at 110° C. for 24 h. 500 ml of 1 mol / L ferric sulfate solution was added to the product after the hydrothermal reaction, and the product was dried by rotary evaporation. The dried product was annealed at 900° C. for 1 h under an inert atmosphere. After the annealing, a 1 M hydrochloric acid solution was used for pickling at 80° C. for 7.5 h to obtain a polymer material.
[0078] (2) Preparation of coating slurry:
[0079] Add the polymer material prepared in step (1), polyethylene glycol and polyvinylidene fluoride into water, stir at high speed to mix evenly, and prepare a coating slurry; in the coating slurry, the polymer material content is 75wt%, the polyethylene glycol content is 12wt%, and the polyvinylidene fluoride content is 13wt%.
[0080] (3) Preparation of porous and highly wettable lithium battery separator:
[0081] The coating slurry obtained in step (2) is sprayed on a 10 μm thick single-layer polypropylene porous membrane, and the coating layer thickness is 6 μm. After drying in an oven, a porous and highly wettable lithium battery separator is obtained.
[0082] Example 10
[0083] This embodiment provides a porous high-wettability lithium battery separator and a preparation method, which are as follows:
[0084] (1) Preparation of polymer materials:
[0085] 200 g of 2-aminothiazole was dissolved in 5000 ml of water, and 1500 ml of 8% sodium hypochlorite solution was added. After mixing evenly, the mixture was transferred into a stainless steel autoclave lined with polytetrafluoroethylene, and hydrothermally reacted at 110° C. for 24 h. 1000 ml of 1 mol / L ferric chloride solution was added to the product after the hydrothermal reaction, and the product was dried by rotary evaporation. The dried product was annealed at 900° C. for 1 h under an inert atmosphere. After the annealing, a 1 M hydrochloric acid solution was used for pickling at 80° C. for 7.5 h to obtain a polymer material.
[0086] (2) Preparation of coating slurry:
[0087] Add the polymer material prepared in step (1), polyethylene glycol and polyvinylidene fluoride into water, stir at high speed to mix evenly, and prepare a coating slurry; in the coating slurry, the polymer material content is 75wt%, the polyethylene glycol content is 12wt%, and the polyvinylidene fluoride content is 13wt%.
[0088] (3) Preparation of porous and highly wettable lithium battery separator:
[0089] The coating slurry obtained in step (2) is hot pressed onto a 20 μm thick single-layer polypropylene porous membrane, and the coating layer thickness is 4 μm. After being dried in an oven, a porous high-wettability lithium battery separator is prepared.
[0090] Embodiment 11
[0091] This embodiment provides a porous high-wettability lithium battery separator and a preparation method. The difference between this embodiment and Example 1 is that: in step (2), the polymer content used is 55wt%, the dispersant is acrylate, the content is 20wt%, and the adhesive is polyvinyl alcohol, the content is 25wt%.
[0092] Example 12
[0093] This embodiment provides a porous high-wettability lithium battery separator and a preparation method. The difference between this embodiment and Example 1 is that: in step (2), the polymer content used is 65wt%, the dispersant is polyacrylate, the content is 15wt%, the adhesive is acrylonitrile multipolymer, the content is 20wt%, and the solvent used is ethanol.
[0094] Example 13
[0095] This embodiment provides a porous high-wettability lithium battery separator and a preparation method. The difference between this embodiment and Example 1 is that: in step (2), the polymer content used is 85wt%, the dispersant is polyvinyl pyrrolidone, the content is 5wt%, the adhesive is acrylonitrile multipolymer, the content is 10wt%, and the solvent used is ethanol.
[0096] Embodiment 14
[0097] This embodiment provides a lithium battery separator and a preparation method. The difference between this embodiment and Example 1 is that when preparing the polymer material, a hydrothermal reaction is carried out in a sodium chlorite solution.
[0098] Embodiment 15
[0099] This embodiment provides a lithium battery separator and a preparation method. The difference between this embodiment and Example 1 is that when preparing the polymer material, a hydrothermal reaction is carried out in a hydrogen peroxide solution.
[0100] Comparative Example 1
[0101] This comparative example provides a lithium battery separator and a preparation method. The difference between this comparative example and Example 1 is that 2-aminothiazole is replaced by ordinary carbon black.
[0102] Comparative Example 2
[0103] This comparative example provides a lithium battery separator and a preparation method. The difference between this comparative example and Example 1 is that when preparing the polymer material, no oxidant solution is added for hydrothermal reaction, and ferric chloride is directly added for polymerization reaction.
[0104] Comparative Example 3
[0105] This comparative example provides a lithium battery separator and a preparation method. The difference between this comparative example and Example 1 is that when preparing the polymer material, only sodium hypochlorite solution is added for hydrothermal reaction, and ferric chloride is not added for polymerization reaction.
[0106] The porous and highly wettable lithium battery separators prepared according to Examples 1-13 and the lithium battery separators prepared according to Comparative Examples 1-3 were tested for porosity and contact angle performance. The porosity test was based on GB / T 21650.1, the contact angle test was based on GB / T30693-2014, the test liquid was the national standard electrolyte, and the test surface was the side coated with the prepared material. The specific data are shown in Table 1.
[0107] Table 1 Comparison of performance of lithium ion battery separators
[0108] Porosity Contact Angle (Electrolyte) Example 1 40% 10° Example 2 38% 12° Example 3 35% 11° Example 4 39% 12° Example 5 29% 12° Example 6 30% 13° Example 7 32% 12° Example 8 39% 8° Example 9 42% 10° Example 10 41% 17° Embodiment 11 33% 12° Example 12 41% 9° Embodiment 13 42% 9° Embodiment 14 41% 9° Embodiment 15 40% 10° Comparative Example 1 33% 45° Comparative Example 2 32% 42° Comparative Example 3 33% 43°
[0109] According to the data in Table 1, Example 5 adopts a roller coating process and Example 6 adopts a scraping process. The porosity is reduced compared with the spraying process, but the structure and composition of the polymer slurry do not change much, and the contact angle is not significantly changed compared with Examples 1-4. Example 7 adopts a spin coating process, the thickness of the base film increases, and the porosity is close to the porosity of the base film. In Example 8, the content of sodium hypochlorite is increased, the degree of polymerization of the polymer is increased, and the contact angle with the electrolyte is reduced. Example 9 changes the source of the iron source, which can still play a role in increasing the porosity and increasing the wetting. Example 10 adopts a hot pressing process, the effect between the coating and the base film is weak, and the contact angle is reduced to a small extent. Examples 11-13 show that under the conditions of 50-90wt% of the polymer material content in the coating slurry, 5-20wt% of the dispersant content, and 5-25wt% of the binder content, as the proportion of polymer material increases, the porosity and contact angle change or decrease slightly. Examples 14-15 only change the type of oxidant, which has no significant effect on the polymerization reaction of the polymer, so the porosity and contact angle do not change much.
[0110] During the preparation process in Comparative Examples 1-3, the polymer failed to be effectively polymerized and could not form a regular morphology, and did not play an effective role in modifying the diaphragm, resulting in the porosity and contact angle of the diaphragm maintaining the characteristics of the base film itself.
[0111] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A porous and highly wettable lithium battery separator, characterized in that: The invention comprises a polyolefin membrane and a polymer material loaded on the polyolefin membrane; the polymer material is obtained by adding imidazole or thiazole organic small molecules into an oxidant solution for hydrothermal reaction, and then adding iron salt for polymerization reaction; the oxidant is sodium hypochlorite, sodium chlorite and hydrogen peroxide.
2. The porous high wettability lithium battery separator according to claim 1, characterized in that: The imidazole or thiazole organic small molecules include one or more of imidazole, thiazole, N-methylimidazole, 2-methylimidazole, 2-phenylimidazole, 2-aminothiazole, 4-methylimidazole, 4-aminothiazole, 5-methylimidazole, and 2-amino-5-methylthiazole.
3. The method for preparing a porous high-wettability lithium battery separator according to claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of polymer materials: adding imidazole or thiazole organic small molecules to an oxidant solution for hydrothermal reaction, and then adding iron salt for polymerization reaction; (2) Preparing a porous and highly wettable lithium battery separator: The polymer material prepared in step (1) is stirred and evenly mixed with a dispersant and a binder in a solvent to obtain a coating slurry, and the coating slurry is then coated on a polyolefin separator and dried to obtain a porous and highly wettable lithium ion battery separator.
4. The method for preparing a porous high-wettability lithium battery separator according to claim 3, characterized in that: The hydrothermal reaction time is 12-48 hours, and the hydrothermal reaction temperature is 90-150°C; the polymerization reaction time is 30-180 minutes, and the polymerization reaction temperature is 700-1000°C.
5. The method for preparing a porous high-wettability lithium battery separator according to claim 3, characterized in that: The mass ratio of the organic small molecule: sodium hypochlorite: iron salt is (10-20): (8-18): (9-22).
6. The method for preparing a porous high-wettability lithium battery separator according to claim 3, characterized in that: The dispersant includes one or more of polyacrylate, polyacrylate, polyethylene glycol, and polyvinyl pyrrolidone; the adhesive includes one or more of polyvinylidene fluoride, styrene-butadiene rubber, acrylonitrile multipolymer, polyvinyl alcohol, polyacrylic acid, polypropylene alcohol, acrylic adhesive, and vinyl acetate adhesive; the solvent includes one or more of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, acetone, dichloromethane, chloroform, N-methylpyrrolidone, dimethyl sulfoxide, cyclohexane, water, and ethanol.
7. The method for preparing a porous high-wettability lithium battery separator according to claim 1, characterized in that: The coating slurry contains 50-90 wt % of polymer material, 5-20 wt % of dispersant and 5-25 wt % of binder.
8. The method for preparing a porous high-wettability lithium battery separator according to claim 1, characterized in that: The polyolefin separator is one or more of a single-layer polypropylene porous membrane, a single-layer polyethylene porous membrane, a multi-layer polyethylene microporous membrane, and a polypropylene-polyethylene multi-layer composite membrane; the coating method includes one of scraping, roller coating, spraying, spin coating, suction filtration, casting, and hot pressing.
9. The porous high wettability lithium battery separator according to claim 3, characterized in that: The thickness of the polyolefin separator is 5-25 μm; the coating thickness is 0.5-20 μm.
10. Application of the porous high wettability lithium battery separator prepared by the method for preparing the porous high wettability lithium battery separator according to any one of claims 3 to 9 in lithium batteries.
Citation Information
Patent Citations
Diaphragm, preparing method of diaphragm and lithium ion battery
CN104078633A
Preparation method of high-wettability lithium ion battery diaphragm
CN113113728A
Nitrogen-sulfur double-doped hollow sphere hard carbon negative electrode material, preparation method and application
CN118495517A
Method for manufacturing separator, separator obtained therefrom, and electrochemical device comprising same
CN118648178A
A method for manufacturing a separator for a lithium secondary battery and the separator fabricated by the same
KR1020160051664A
Cited By
Composite diaphragm, preparation method thereof and sodium ion battery
CN120749351A
